Serological survey of Chlamydia abortus in Greek dairy sheep flocks - Petridou, EJ; Kiossis, E; Chochlakis, D; Lafi, SQ; Psaroulaki, A; Filippopoulos, LK; Baratelli, M; Giadinis, ND (Journal of the Hellenic Veterinary Medical Society, 2022)
Chlamydiosis due to Chlamydia abortus is one of the most common causes of abortion in small ruminant flocks worldwide. Although the causative agent is zoonotic, chlamydiosis is not a reportable disease. There is lack of recent data concerning sheep chlamydiosis in Greece. In the current study, a serological investigation for Chlamydia abortus was conducted. Blood samples from 26 randomly selected sheep flocks not vaccinated against chlamydiosis were collected. From each flock, 15 to 20 blood samples were taken from adult female sheep. In total 464 blood samples were examined. One hundred and six samples were positive (22.8%), while 24 samples (5.24%) were doubtful. Moreover, at farm level, in 18 out of the total number of 26 farms, at least one positive animal was detected (69.2%). Chlamydiosis is considered a highly likely cause of sheep abortion in Greece. Therefore, vaccination of the sheep flocks is strongly recommended for the prevention and control of the disease.